ความสัมพันธ์ระหว่างปัจจัยส่วนบุคคล ความสามารถในการเผชิญและฟันฝ่าอุปสรรค การสนับสนุนจากครอบครัว กับความสำเร็จในวิชาชีพ ของหัวหน้าหอผู้ป่วย โรงพยาบาลศูนย์ - นภดล คำเติม (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study career success of head nurses in Regional Hospital and Medical Centers. And to investigate the relationships between personal factors, adversity quotient, family support, and career success of head nurses, and thirdly, to search for the variables that could be able to predict career success of head nurses. The sample consisted of 345 head nurses selected by multi-stage sampling technique. Research instruments were the three parts of questionnaires: career success, adversity quotient, and family support. The instruments were tested for content validity by the experts and their reliability were .87, .84, and .94 respectively. Statistical methods used to analyze the data included arithmetic mean, standard deviation, Contingency Coefficient, Pearson{174}s Correlation Coefficient, and Stepwise Multiple Regression Analysis. Major finding were as follows: 1. Career success of head nurses in Regional Hospital and Medical Centers was at the high level (X= 3.92). 2. Personal factors of head nurses were not related to career success. 3. Adversity quotient and family support were positively and significantly related to career success of head nurses at the .05 level (r =.331 and .337 respectively). 4. Factors significantly predicted career success of head nurses were family support, and adversity quotient at the .05 level. These predictors were accounted for 18.6% of the variance (R2 = .186). The standardized prediction function derived from the analysis was as follow: Z Career Success = .282 Z family support +.274 Z adversity quotient.